2009
DOI: 10.1186/1746-160x-5-21
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of intravenous methylergonovine in migraine female patients attending the emergency department: a pilot open-label study

Abstract: BackgroundMethylergonovine is an ergot alkaloid widely used in postpartum women. It is also an active metabolite of methysergide and previous studies suggest that it could be effective against refractory headache and cluster headache. The purpose of the present study was to assess the potential therapeutic effectiveness of methylergonovine in the emergency treatment of severe migraine.MethodsOne hundred and twenty five female patients with migraine attending the emergency department received 0.15 mg of methyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…According to Braaten et al [ 41 ], intravenous injections of sedatives did not help reduce the pain in patients with surgical abortion during the first trimester; in contrast to their study, due to the administration of combined misoprostol and methylergonovine, severe pain remained uncovered, and its manifestation occurred in none of the patients. It is noteworthy to mention that methylergometrine can also be used to modulate the pain of origins except miscarriage; for example, Niño-Maldonado et al reported positive efficacy of methylergometrine for migraine pain modulation in emergency settings [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Braaten et al [ 41 ], intravenous injections of sedatives did not help reduce the pain in patients with surgical abortion during the first trimester; in contrast to their study, due to the administration of combined misoprostol and methylergonovine, severe pain remained uncovered, and its manifestation occurred in none of the patients. It is noteworthy to mention that methylergometrine can also be used to modulate the pain of origins except miscarriage; for example, Niño-Maldonado et al reported positive efficacy of methylergometrine for migraine pain modulation in emergency settings [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylergonovine is the active metabolite of Methysergide and is 40 times more potent (11). It is a semisynthetic ergot alkaloid widely used in the treatment of postpartum hemorrhage (12, 13) as well as the prophylaxis of migraines (13). It acts as an agonist for 5HT1 receptors (6, 13) and antagonist of 5HT2 receptors on the temporal artery (11).…”
Section: Discussionmentioning
confidence: 99%